Pengaruh Diversifikasi Kredit terhadap Risiko Kredit dan Profitabilitas Pada Bank Pembangunan Daerah di Indonesia - Allanda, Mohammad Reza; Arisyahidin, Arisyahidin; Mega Hastuti, Sri Wahyu (Otonomi, 2024)
Regional Development Banks have a role in supporting the economy of a region, namely as an access provider of capital for individuals and business entities in the form of credit. In carrying out the intermediation function, banks are required to apply the principle of prudence in distributing credit to debtors. One of the current issues is that there has been a shift in BPD's business strategy, which previously relied on the consumer credit sector, but is now starting to shift to the productive sector. This cannot be separated from the credit distribution diversification strategy so that it is more optimal and does not rely on just one sector. This research will test whether credit diversification has an effect on credit risk and profitability at Regional Development Banks (BPD) in Indonesia. This research uses a quantitative research approach. The data used in this research is secondary data from financial reports released by BPD for the 2020-2023 period. The population in this research is the Regional Development Banks in Indonesia, namely 27 banks. The sampling of companies in this research used a purposive sampling method, resulting in a sample of 22 banks. The results of the research show that credit diversification has a negative and significant influence on credit risk variables. In addition, credit diversification has a positive and significant influence on the profitability variable (ROA).